(untitled) (International relations and international law Journal, 2021)
Migration and migration policy go hand in hand and every country on earth sets policies to regulate it. When migrants are well managed, they significantly contribute to sustainable development of both hosting and origin country. Regional integration and globalization process are also drivers of migration and cannot be left behind, though mostly the reasons are to find out good standards of living. This study “Recent trends of Migration to Rwanda: Policy and contribution to sustainable development” had aim to analyze recent trends of migration to Rwanda starting with a brief historical context and moving on to current sustainable developments. This paper also discussed broad trends in the rates and levels of migration to Rwanda over the past decade, the destination they chose on arrival to Rwanda; and policy implication of these trends. It also served as a tool for policymakers working on migration issues in Rwanda to help clarify the basis of current migration policy and indicate the potential of the existing framework for development-oriented approach to migration management in Rwanda. The results showed that migration and migration policy in Rwanda had contributed to sustainable development in Rwanda. The results showed that those immigrants with necessary skills greatly contribute to the Rwanda sustainable development by doing jobs that Rwandans cannot do and pay high taxes to the Government. The government also gains taxes and Rwandans learn from their counterparts from the regions. Skilled migration to Rwanda played an important role in filling labor needs in various sectors of the economy that are essential for Rwanda economic growth and development. Key words: migration, sustainable development, migration policy, regional integration, immigrants.